1993
DOI: 10.1021/ja00066a032
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen binding site in hydrogenase: 35-GHz ENDOR and XAS studies of the nickel-C (reduced and active form) and the Ni-L photoproduct

Abstract: EPR, 35-GHz ENDOR, and X-ray absorption (XAS) spectroscopic studies of H2 binding in hydrogenase from Thiocapsa roseopersicina are reported. These studies involve spectra taken on an active form of the enzyme that displays an EPR signal designated Ni-C. This form of the enzyme is light sensitive and is converted to a photoproduct that exhibits a unique EPR signal, Ni-L. 'H-ENDOR spectra reveal two sets of protons that interact strongly with the EPR-active center in Ni-C. The first proton set (HI) is solvent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
150
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(165 citation statements)
references
References 1 publication
15
150
0
Order By: Relevance
“…Eidsness et al [56,57] concluded for the D. gigas enzyme that the coordination would be tetragonally-distorted octahedral or trigonalbipyramidal, in line with earlier conclusions based on the EPR spectra of Ni(III) in several hydrogenases [7,29,144]. Maroney and coworkers came to a similar conclusion from X-ray absorption studies on the T. roseopersicina enzyme [18,136,137,224,225].…”
Section: Sulphur Oxygen and Nitrogensupporting
confidence: 57%
See 4 more Smart Citations
“…Eidsness et al [56,57] concluded for the D. gigas enzyme that the coordination would be tetragonally-distorted octahedral or trigonalbipyramidal, in line with earlier conclusions based on the EPR spectra of Ni(III) in several hydrogenases [7,29,144]. Maroney and coworkers came to a similar conclusion from X-ray absorption studies on the T. roseopersicina enzyme [18,136,137,224,225].…”
Section: Sulphur Oxygen and Nitrogensupporting
confidence: 57%
“…Maroney and coworkers [225] have repeated and extended the ENDOR measurements with the T. roseopersicina enzyme displayed an isotropic coupling and were ascribed to /3-CH 2 protons from a cysteine residue [225].…”
Section: Favoured Binding Of Dihydrogen To Ni A(i)mentioning
confidence: 98%
See 3 more Smart Citations